Environmental, social and governance [ESG] consulting model - Trentin, Luciano; Marques, Moacir (Revista de Administração da UFSM, 2025)
Purpose: This study proposes to develop a consultancy model to evaluate the level of maturity of ESG practices. Design/Methodology/approach: Business Model Canvas [ESG] as a framework for creating a business model focusing on Environmental, Social and Governance [ESG] consultancy services. A five-level maturity scale was applied to the dimensions that characterize the diagnostic checklist model for ESG practices. The Delphi research method was used to evaluate the content of the diagnostic checklist for ESG practices. Findings: As a result, a hypothetical consultancy called ENGES Consulting Ltda. was created, constituted through the creation of the social contract, creation of the mission, vision and values, in addition to the development of a business model based on the Business Model Canvas strategic management tool [BMC] A checklist model was also created for diagnosing ESG practices and their respective maturity level. Originality/relevance: The relevance and contribution of this study in the scientific aspect lies in the proposal of a consultancy model to assess the maturity level of ESG practices in disparate organizations. Practical implications: The practical contribution lies in understanding Environmental, Social and Governance [ESG] management practices based on the ESG practices diagnosis checklist model and the respective level of maturity, identifying strengths and points that demonstrate implementation or execution weaknesses, in addition to providing a way to compare results (benchmarking) obtained between organizations.